The visual quality of Cozumel beach landscapes evaluated through the eyes of the observer - López Contreras, Cruz (2022)
The beaches scenic beauty influences the selection of a sun and beach destination. Due to the large flows of national and international tourists, the beaches are economically and culturally important, so it is relevant to know the attributes that determine the preference for these sites. The objective of this research is to assess 10 landscapes of the Cozumel beach through the visual preferences of potential tourists and resident population. For this, the peer test is used, and other instruments for the evaluation and analysis of the answers of the interviewees. The results show that both groups value, in a higher percentage, sandy beaches without anthropic elements and with vegetation; In addition, they prioritize tranquillity and few people on a beach. They also show that the preference of the residents is influenced by the identity that the community has towards the traditionally visited beaches.